BIOCHEMICAL GENETICS OF TIGER SHRIMP Penaeus rnonodon: DESCRIPTION OF ELECTROPHORETIC DETECTABLE LOCI - Ketut Sugama; Haryanti Haryanti; Fuad Cholik (Research Center for Fisheries, 1996)
As part of a search for biochemical genetic markers for tiger shrimp, Penuuemorndon, wild shrimp were collected from the coastal waters of Aceh, Bali and Sumbawa, (Nusa Tenggara Barat).